A Comparative Study Between Students’ Using Video And Audio Media In Listening - Tiodora Silalahi; Erwin Sandyadenta (Program Studi Pendidikan Bahasa Inggris FKIP, 2022)
The objective of this research is to find out significant difference between students’ listening comprehension ability using video and audio media. This research was a quantitative research. This research was conducted to the second grade students of SMP N 7 Pematangsiantar. In this research, researcher using pre-experimental class. As the sample of this research, the researcher took class VII-F as the experimental class. The sample was chosen randomly under the assumption that each class had the same level of ability. In collecting the data, the researcher used multiple choice items. The data were analyzed by using Microsoft excel and some formula to calculating the mean score and standard deviation of student test. The researcher found that there is a relative difference of the students’ listening comprehension achievement between the students who were using video and those who using audio. It can be seen from the mean score of the student In video test the mean score is 76,41 meanwhile in audio test the mean score of the student is 77,96. In standard deviation video test got the result 2,35 and audio test got 19,96. Furthermore, based on the result of the data, teaching listening through audio is more effective to increase students’ listening comprehension because audio can give more concentration for the students in the classroom. When the students listen using audio media, they are can focus to the story. This situation creates a more active class and pleasurable study for them to learn and comprehend the listening skill. The audio is also able to motivate them to the lesson in the class